2001
DOI: 10.1097/00004691-200103000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cortical θ Activity and Hippocampal Volumes in Health, Mild Cognitive Impairment, and Mild Dementia

Abstract: Cognitive decline is known to be associated with both increased theta power over frontal regions and hippocampal atrophy. The aim of this study was to reveal the relation between these parameters in groups with mild dementia, mild cognitive impairment, and healthy control subjects. The authors examined a preliminary randomly selected sample of 39 right-handed subjects joining the Leipzig Longitudinal Study of the Aged, consisting of 17 normal elderly subjects, 12 patients with mild cognitive impairment, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 31 publications
7
57
0
1
Order By: Relevance
“…182 This volume loss was also significantly greater in demented patients compared with both cognitive impaired and elderly control subjects. Similarly, Grunwald et al 183 found hippocampal volume loss in dementia, and Barber et al 184 found a loss of hippocampal asymmetry in patients with dementia with Lewy bodies (DLB) (as well as AD patients) compared to normal controls. Volumetric MRI of the brain in elderly subjects with lacunes, mild cognitive impairment, a group of patients with dementia, and a group with probable AD revealed hippocampal volume loss in all three patient groups.…”
Section: Dementiamentioning
confidence: 92%
“…182 This volume loss was also significantly greater in demented patients compared with both cognitive impaired and elderly control subjects. Similarly, Grunwald et al 183 found hippocampal volume loss in dementia, and Barber et al 184 found a loss of hippocampal asymmetry in patients with dementia with Lewy bodies (DLB) (as well as AD patients) compared to normal controls. Volumetric MRI of the brain in elderly subjects with lacunes, mild cognitive impairment, a group of patients with dementia, and a group with probable AD revealed hippocampal volume loss in all three patient groups.…”
Section: Dementiamentioning
confidence: 92%
“…There is evidence that EEG power in the alpha band declines with AD-related cognitive impairment [293]. Other studies have shown enhanced low-frequency brain oscillation in the theta [294] and delta bands in temporal and occipital areas as well as reduction of beta power in temporal and occipital areas in MCI [295]. However, frequency band-power methods need to address some current limitations, notably regarding the necessity to adjust band limits depending on task and individual, as well as to study more completely each band's significance in relation to neuronal phenomena.…”
Section: Resting-state Neuroelectrical/neuromagnetic Markersmentioning
confidence: 99%
“…In fact, progressive neocortical and hippocampal atrophy were described in PE patients (Mathern et al, 2002;Cendes, 2005) but hippocampal quantitative MRI data and the theta measures have never been correlated in PE. This was done in Alzheimer's disease where negative linear correlation was found between hippocampal body volume and theta power over the frontal regions (Grunwald et al, 2001). …”
Section: Patients Under Medication (Group2)mentioning
confidence: 99%
“…However, regional theta power correlates positively to the volume of cerebral edema around brain lesions (Fernandez-Bouzas et al, 1997) and negatively to hippocampal volumes in Alzheimer's disease (Grunwald et al, 2001). …”
Section: Introductionmentioning
confidence: 99%